Method for preparing ultrafine spherulitic calcium carbonate using biogas slurry

CN118183816BActive Publication Date: 2026-10-30CHINA THREE GORGES CORPORATION
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410338238.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-22
Publication Date
2026-10-30
Estimated Expiration
2044-03-22

AI Technical Summary

Technical Problem

在实际作业中,沼液的回收利用存在较大的困难,导致大部分沼液被作为废弃物重新排放到环境中,造成了二次污染

Benefits of technology

[0017]如上所述的方法,其中,絮凝处理包括使用无机絮凝剂、有机絮凝剂中的至少一种进行絮凝处理。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118183816B_ABST
    Figure CN118183816B_ABST
Patent Text Reader

Abstract

The application provides a method for preparing superfine ball spar type calcium carbonate by using biogas slurry. The method comprises the following steps: 1) adding gypsum into the biogas slurry to form a mixture, then introducing carbon dioxide gas, and obtaining a first material after the reaction is completed; wherein the pH of the biogas slurry is 8-10, the content of suspended solids is less than or equal to 2000 mg / L, and the content of ammonium nitrogen is greater than or equal to 1000 mg / L; 2) performing solid-liquid separation on the first material, and performing drying treatment on the obtained solid to obtain the superfine ball spar type calcium carbonate with a crystal grain size of 25-30 nm, wherein the temperature of the drying treatment is 150-600 DEG C. The superfine ball spar type calcium carbonate can be obtained through the method, and a new idea is provided for the reuse of biogas slurry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for preparing ultrafine spherical aragonite-type calcium carbonate using biogas slurry, belonging to the field of calcium carbonate preparation technology. Background Technology

[0002] With the restructuring of agricultural industrialization and the implementation of new rural construction, my country's rural biogas projects have developed rapidly in the past decade. While the benefits of biogas projects have become apparent, a large amount of biogas fermentation byproducts—biogas slurry—has been generated. Biogas slurry is the liquid residue after the anaerobic fermentation of livestock and poultry manure. It is generally weakly alkaline and contains a large amount of organic matter, nitrogen, phosphorus, potassium, and other nutrients. In practice, the recycling and utilization of biogas slurry presents significant difficulties, resulting in most of it being discharged back into the environment as waste, causing secondary pollution.

[0003] Calcium carbonate is a valuable resource with a wide range of applications, widely used in the manufacture of cement, lime, calcium carbide, and in the metallurgical industry. Ultrafine calcium carbonate is a classification of calcium carbonate, and its unique quantum size effect, small size effect, and surface effect give it significant advantages over conventional powder materials in terms of reinforcement, transparency, dispersibility, thixotropy, and leveling. Spheroidal aragonite is one of the common crystal forms of calcium carbonate. In addition to conventional properties such as low density, white and odorless color, acid decomposition, and chemical stability, spheroidal aragonite calcium carbonate also possesses advantages such as hollow or porous structure, uniform particle size distribution, micro-nano size, high hydrophilicity, large specific surface area, good solubility and dispersibility, good biocompatibility and safety, good degradability, strong phase transformation ability, good mechanical properties and thermal stability, and spherical distribution. Therefore, ultrafine spheroidal aragonite calcium carbonate has great application prospects and economic benefits in daily life, biomedicine, and new materials.

[0004] The preparation of ultrafine spherical calcium carbonate from biogas slurry has become a research hotspot in this field. Summary of the Invention

[0005] This invention provides a method for preparing ultrafine spheroidal calcium carbonate using biogas slurry. This method can produce ultrafine spheroidal calcium carbonate from biogas slurry, providing a new approach for the recycling of biogas slurry and the preparation of ultrafine spheroidal calcium carbonate. The method is simple to operate and conducive to industrial application.

[0006] This invention provides a method for preparing ultrafine spherical aragonite-type calcium carbonate using biogas slurry, comprising the following steps:

[0007] 1) Add gypsum to the biogas slurry to form a mixture, introduce carbon dioxide gas, and obtain the first material after the reaction is complete;

[0008] The biogas slurry has a pH of 8-10, a suspended solids content of ≤2000 mg / L, and an ammonium nitrogen content of ≥1000 mg / L.

[0009] 2) The first material is subjected to solid-liquid separation, and the obtained solid phase is dried to obtain the ultrafine spherical aragonite-type calcium carbonate with a crystal size of 25-30 nm, wherein the drying temperature is 150-600℃.

[0010] The method described above, prior to step 1), further includes pretreatment of the biogas slurry stock solution to obtain the biogas slurry;

[0011] The pretreatment includes at least flocculation treatment, pH adjustment treatment, and solid-liquid separation treatment.

[0012] In the method described above, the drying temperature is 169-180°C.

[0013] In the method described above, the carbon dioxide-based gas includes at least one of the following: flue gas from coal combustion, flue gas from gas combustion, a mixture of carbon dioxide and nitrogen, and pure carbon dioxide gas.

[0014] In the method described above, the volume concentration of carbon dioxide in the carbon dioxide-based gas is >10%.

[0015] In the method described above, in step 1), the flux of carbon dioxide into the radial cross-section of the reaction system is 0.32-0.64 m / min.

[0016] In the method described above, the mass ratio of ammonium nitrogen in the gypsum and the biogas slurry is 13:(3-6).

[0017] The method described above, wherein the flocculation treatment includes flocculation treatment using at least one of inorganic flocculants and organic flocculants.

[0018] The method described above, wherein the particle size of the gypsum is ≤45μm.

[0019] In the method described above, in step 2), the solid-liquid separation is centrifugal separation, wherein the centrifugal separation speed is 800-1200 r / min and the time is 10-20 min.

[0020] This invention achieves the production of ultrafine spheroidal aragonite-type calcium carbonate by limiting the pH, suspended solids, and ammonium nitrogen content of biogas slurry, thereby enabling the biogas slurry to absorb carbon dioxide and promote the reaction between carbon dioxide and gypsum. Simultaneously, by limiting the drying temperature to 150-600℃, the crystal form of the ultrafine spheroidal aragonite-type calcium carbonate remains stable during the drying process, which is beneficial for improving product yield and purity. This invention provides a new approach for the recycling of biogas slurry and the preparation of ultrafine spheroidal aragonite-type calcium carbonate; the method is simple to operate and conducive to industrial-scale application. Attached Figure Description

[0021] Figure 1 A schematic diagram of a process for preparing ultrafine spherical aragonite-type calcium carbonate using biogas slurry;

[0022] Figure 2 Here are electron microscope images of the product from Example 1;

[0023] Figure 3 Electron microscope images of the product in Example 2;

[0024] Figure 4 Here are electron microscope images of the product from Example 3;

[0025] Figure 5 Here is an electron microscope image of the product from Example 4;

[0026] Figure 6 Electron microscope images of the product in Comparative Example 1;

[0027] Figure 7 Electron microscope images of product 2 (Comparative Example 2);

[0028] Figure 8 The XRD pattern of the product in Example 1;

[0029] Figure 9 The XRD pattern of the product in Example 2;

[0030] Figure 10 The XRD pattern of the product in Example 3;

[0031] Figure 11 The XRD pattern of the product in Example 4;

[0032] Figure 12 The XRD pattern of the product in Comparative Example 1;

[0033] Figure 13 The image shows the XRD pattern of product 2 in Comparative Example 2. Detailed Implementation

[0034] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions in the embodiments of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0035] This invention provides a method for preparing ultrafine spherical aragonite-type calcium carbonate using biogas slurry, comprising the following steps:

[0036] 1) Add gypsum to the biogas slurry to form a mixture, introduce carbon dioxide gas, and obtain the first material after the reaction is complete;

[0037] Among them, the pH of the above-mentioned biogas slurry is 8-10, the content of suspended solids is ≤2000mg / L, and the content of ammonium nitrogen is ≥1000mg / L;

[0038] 2) The first material is subjected to solid-liquid separation, and the obtained solid phase is dried to obtain ultrafine spherical aragonite-type calcium carbonate with a crystal size of 25-30 nm. The drying temperature is 150-600℃.

[0039] The aforementioned biogas slurry is the liquid residue after anaerobic fermentation of livestock and poultry manure. It is generally weakly alkaline and contains a large amount of organic matter, nitrogen, phosphorus, potassium, and other nutrients. Carbon dioxide-based gases refer to gases that include carbon dioxide, which can be pure carbon dioxide or a mixture of carbon dioxide and other components.

[0040] In step 1) above, after the carbon dioxide in the carbon dioxide-based gas is absorbed by the biogas slurry, it exists mostly in the biogas slurry as carbonate ions and a small portion as carbon dioxide molecules. Since the solubility of calcium sulfate in gypsum in the liquid phase is lower than that of calcium carbonate, gypsum can react with carbonate ions or carbon dioxide to form calcium carbonate.

[0041] Carbon dioxide has low solubility in water, making the mass transfer of carbon dioxide from the gas phase to the liquid phase the rate-determining step of the entire reaction process. To increase the rate of carbon dioxide mass transfer from the gas phase to the liquid phase, this invention limits the pH of the biogas slurry to 8-10, enhancing the biogas slurry's ability to absorb carbon dioxide, promoting the formation of ultrafine spheroidal aragonite-type calcium carbonate, and increasing the product formation rate. During the reaction of gypsum with carbonates or carbon dioxide to form calcium carbonate, the ammonium nitrogen in the biogas slurry promotes the formation of spheroidal aragonite-type crystal structures in calcium carbonate, inhibiting the formation of other crystal forms, acting as a crystallization agent. It also affects the size of calcium carbonate particles, promoting the formation of ultrafine spheroidal aragonite-type calcium carbonate with a grain size of 25-30 nm. Suspended solids in the biogas slurry affect the purity of the product and also have a certain impact on the stability of the crystal form and the size of calcium carbonate particles during product formation. The inventors discovered that by limiting the pH of the biogas slurry to 8-10, the content of suspended solids to ≤2000mg / L, and the content of ammonium nitrogen to ≥1000mg / L, the biogas slurry's ability to absorb carbon dioxide was enhanced, and the formation of ultrafine spherical aragonite-type calcium carbonate with a crystal size of 25-30nm was promoted.

[0042] The above grain size refers to the average grain size, which is determined with reference to "Nano Calcium Carbonate" (GB / T19590-2011).

[0043] Step 1) The first material obtained includes the target product of the present invention, ultrafine spherical aragonite-type calcium carbonate, and the by-product ammonium sulfate solution. The ultrafine spherical aragonite-type calcium carbonate has low solubility in the first material and is mostly suspended in the first material in solid form. The by-product ammonium sulfate has high solubility in the first material and exists in solution.

[0044] In step 2), the first material is subjected to solid-liquid separation to obtain a solid phase and a liquid phase. The main components of the solid phase are ultrafine spherical aragonite-type calcium carbonate and a small amount of water, while the main component of the liquid phase is ammonium sulfate solution. This invention is not limited to the above-mentioned solid-liquid separation method; for example, centrifugation, vacuum filtration, or other pressure filtration methods can be used.

[0045] The crystal structure of aragonite-type calcium carbonate is unstable and easily transforms into other crystal forms, especially during the solid-phase drying process. Water molecules readily exert forces on the calcium carbonate crystals, causing the aragonite-type crystal structure to transform into the calcite-type. The inventors discovered that limiting the drying temperature to 150-600℃ helps ensure that the aragonite-type calcium carbonate maintains a stable crystal structure during the drying process and does not undergo crystal transformation.

[0046] The present invention does not limit the equipment used for the above-mentioned drying process; for example, a common oven or other drying equipment may be used.

[0047] The above preparation method utilizes biogas slurry as a carbon dioxide absorption medium and gypsum as the main carbon dioxide fixative. It controls the morphology of calcium carbonate crystals by leveraging the crystallization effect of ammonium nitrogen in biogas slurry, efficiently capturing carbon dioxide gas and converting it into high-value-added ultrafine spherical aragonite-type calcium carbonate, while also producing ammonium carbonate solution. This allows for the reuse of biogas slurry, reduces reaction costs, and is simple and convenient to operate. It has high economic, social and environmental benefits and has high promotion value.

[0048] Generally, biogas slurry also contains some small-molecule organic matter, such as proteins, amino acids, growth hormones, sugars, vitamins and various hydrolytic enzymes. These small-molecule organic matter also act as crystallizing agents, which is conducive to the formation of ultrafine spherical aragonite-type calcium carbonate.

[0049] Evenly dispersing gypsum in biogas slurry facilitates a full reaction between the dissolved carbon dioxide and gypsum, improving the utilization rate of both. Therefore, after adding gypsum to the biogas slurry, thorough stirring is necessary to promote its even dispersion. The stirring speed can be 200-400 r / min, for example, 200, 250, 300, 350, or 400 r / min, and the stirring time can be 20-30 min, for example, 20, 25, or 30 min. By controlling these parameters, this invention not only ensures the full dispersion of gypsum in the biogas slurry but also avoids excessively long stirring times and excessively high stirring speeds that would increase energy consumption.

[0050] In some embodiments, the gypsum described above is desulfurized gypsum generated by the desulfurization unit of a coal-fired power plant. The desulfurized gypsum has a small average particle size, which provides numerous nucleation sites for the formation of ultrafine spheroidal aragonite-type calcium carbonate, thus improving the product preparation rate. Therefore, this invention provides a new method for the treatment of desulfurized gypsum, realizing the resource utilization of desulfurized gypsum, reducing reaction costs, and possessing high economic, social, and environmental benefits, making it highly valuable for widespread application.

[0051] Furthermore, to improve product purity, after solid-liquid separation, the solid phase is washed with deionized water. After washing, the solid phase is centrifuged again, and this process is repeated 2-3 times to remove impurity ions from the solid phase surface. Since the impurity ions include sulfate ions, barium chloride solution can be used to test the washing solution. If no white precipitate is found, it indicates that the impurity ions have been thoroughly washed away.

[0052] The ammonium sulfate solution, a byproduct of this invention, can be used directly as fertilizer, for example, for watering garden plants; it can also be concentrated and crystallized to prepare ammonium sulfate fertilizer, thus maximizing resource utilization.

[0053] Biogas slurry stock solution is a byproduct of biogas fermentation, including at least one of the following: fresh biogas slurry after anaerobic fermentation, biogas slurry after solid-liquid separation, and biogas slurry aged in a biogas slurry pond for a period of time. Because the composition of biogas slurry stock solution is very complex, with many solid impurities, and its pH, suspended solids content, and ammonium nitrogen content may not meet the above-mentioned limitations, it is not suitable for directly using biogas slurry stock solution to prepare ultrafine spherical aragonite-type calcium carbonate. Therefore, before step 1), the biogas slurry stock solution is pretreated to obtain the aforementioned biogas slurry; wherein the pretreatment includes at least flocculation treatment, pH adjustment treatment, and solid-liquid separation treatment.

[0054] The suspended solids content in biogas slurry is generally higher than 2000 mg / L. Excessive suspended solids will affect the quality of the product and are not conducive to the formation of ultrafine spherical aragonite-type calcium carbonate. Therefore, when the suspended solids content in biogas slurry exceeds 2000 mg / L, the biogas slurry needs to be flocculated to improve the quality of the product and promote the formation of ultrafine spherical aragonite-type calcium carbonate.

[0055] To ensure that the suspended solids content in biogas slurry is ≤2000mg / L, the raw biogas slurry can be subjected to multiple flocculation treatments until its suspended solids content is ≤2000mg / L.

[0056] The purpose of pH adjustment treatment is to adjust the pH of the biogas slurry to 8-10. In some embodiments, pH adjustment treatment is carried out by adding calcium oxide, which helps to avoid the introduction of impurity ions.

[0057] Solid-liquid separation can remove large particulate solid impurities from biogas slurry. This invention does not limit the specific method of solid-liquid separation mentioned above; for example, centrifugation and filtration can also be applied to this invention.

[0058] The above pretreatment can be carried out in a chemical dosing and dehydration integrated machine.

[0059] In summary, the above pretreatment of biogas slurry can produce biogas slurry suitable for preparing ultrafine spherical aragonite-type calcium carbonate.

[0060] A schematic diagram of the process for preparing ultrafine spherical aragonite-type calcium carbonate according to the present invention is shown below. Figure 1 As shown.

[0061] Furthermore, the drying temperature described above is 169-180°C, for example, 169, 170, or 180°C.

[0062] A temperature of ℃ is beneficial for maintaining the stability of the product's crystal form during the drying process, enabling rapid drying and obtaining ultrafine spherical aragonite-type calcium carbonate.

[0063] Understandably, excessively long drying time can also affect the stability of the product's crystal form. Therefore, the present invention further limits the drying time to 30-60 min, such as 30, 40, 50 or 60 min, which is beneficial to maintaining the stability of the ultrafine spherical aragonite-type calcium carbonate crystal form.

[0064] The aforementioned carbon dioxide-based gases include flue gas from coal combustion, flue gas from natural gas combustion, other mixtures of carbon dioxide and nitrogen, or pure carbon dioxide gas.

[0065] In some embodiments, the flue gas is flue gas that has undergone flue gas treatment emitted from coal-fired power plants, gas-fired power plants, or other coal-fired or gas-fired plants. The method of the present invention has a good effect on capturing carbon dioxide in flue gas, provides a new method for capturing and fixing carbon in flue gas, solves the problem of carbon dioxide capture and application in flue gas, realizes the utilization of flue gas waste, reduces reaction costs, and has high economic significance and promotion value.

[0066] In some embodiments, the aforementioned carbon dioxide-based gas is a mixture of carbon dioxide and nitrogen, used to simulate flue gas with different carbon dioxide contents.

[0067] Since the volume concentration of carbon dioxide in the carbon dioxide-based gas has a crucial impact on the product preparation rate, in order to improve the product preparation rate and reduce the reaction time, this invention limits the volume concentration of carbon dioxide in the aforementioned carbon dioxide-based gas to >10%, for example, the volume concentration of carbon dioxide in the carbon dioxide-based gas can be 15%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% or 100%.

[0068] Since the absorption of carbon dioxide by biogas slurry is the rate-determining step of the entire reaction system, in order to moderately increase the absorption rate of carbon dioxide and maintain the reaction rate of carbon dioxide and gypsum within a suitable range, this invention specifies that in step 1), the flux of carbon dioxide into the radial cross-section of the reaction system is 0.32-0.64 m / min.

[0069] The radial section of the above reaction system refers to the cross section of the reaction system perpendicular to the flow direction of the carbon dioxide gas.

[0070] The flux of carbon dioxide into the radial cross section of the reaction system refers to the flux of carbon dioxide along the flow direction when the radial cross-sectional area of ​​the carbon dioxide gas is equal to that of the reaction system after the carbon dioxide gas has diffused into the reaction system; that is, the flux when carbon dioxide is fully diffused into the radial cross section of the reaction system.

[0071] By limiting the flux of carbon dioxide into the reaction system to 0.32-0.64 m / min in the radial cross section, the rate at which carbon dioxide gas is introduced into the biogas slurry is made appropriate. This avoids the situation where the carbon dioxide absorption and fixation rate is too low due to an excessively high rate, and at the same time avoids the situation where the reaction time is too long due to an excessively low rate. It also helps to control the reaction rate between carbon dioxide and gypsum, and promotes the formation of a large amount of ultrafine spherical aragonite-type calcium carbonate with a grain size of 25-30 nm.

[0072] The carbon dioxide gas introduction time can be controlled according to the actual required amount of carbon dioxide and the introduction rate of the carbon dioxide gas. For example, the carbon dioxide gas introduction time is 120-300 min, and further 150, 180, 210, 240 or 270 min, which is beneficial to control the reaction time and avoid the reaction time being too long.

[0073] Therefore, limiting the radial cross-sectional area and the rate of carbon dioxide gas introduction is essentially aimed at controlling the residence time and amount of carbon dioxide in the reaction system, ensuring efficient reaction and maximizing resource utilization.

[0074] Since gypsum is the main raw material carrier for fixing carbon dioxide to form calcium carbonate, and ammonium nitrogen plays a regulatory role in the grain size and crystal form of calcium carbonate, this invention limits the mass ratio of ammonium nitrogen in gypsum and biogas slurry to 13:(3-6), for example, at least one or any two sets of values ​​between 13 / 3, 13 / 3.5, 13 / 4, 13 / 4.5, 13 / 5, 13 / 5.5, and 13 / 6, preferably 13 / 3, which is beneficial to maximizing the absorption and fixation rate of carbon dioxide, and also beneficial to regulating the grain size and crystal form of calcium carbonate, promoting the formation of ultrafine spheroidal aragonite-type calcium carbonate.

[0075] The carbon dioxide absorption and fixation rate mentioned above is the percentage of the volume of carbon dioxide absorbed by the biogas slurry and the volume of carbon dioxide introduced into the biogas slurry.

[0076] In some embodiments, the above-mentioned flocculation treatment is performed using a flocculant, specifically, at least one of an inorganic flocculant and an organic flocculant. The inorganic flocculant includes at least one of polyaluminum chloride, polyferric chloride, and polyaluminum ferric chloride, while the organic flocculant includes at least one of nonionic polyacrylamide, anionic polyacrylamide, and cationic polyacrylamide. The inventors have found that, compared to inorganic flocculants, organic flocculants have a better flocculation effect on the raw biogas slurry and are more conducive to the formation of ultrafine spherical aragonite-type calcium carbonate; therefore, organic flocculants are preferred. Furthermore, among organic flocculants, cationic polyacrylamide flocculants have a better flocculation effect on the raw biogas slurry; therefore, cationic polyacrylamide flocculants are preferred.

[0077] The amount of flocculant added should be limited according to the type of flocculant and the content of suspended solids in the biogas slurry. For example, the amount of inorganic flocculant added is 0.1, 0.2, 0.4, 0.6, 0.8, 1, 2, 3, 4, 5 g / L or any two of the above values; the amount of organic flocculant added is 1, 2, 5, 10, 20, 50, 100, 200, 400, 500 mg / L or any two of the above values.

[0078] The above-mentioned addition amounts all refer to the mass of flocculant added per unit volume of biogas slurry.

[0079] The present invention does not impose any special limitation on the source of the above-mentioned flocculant, which may be a commercially available flocculant or a flocculant made in the laboratory.

[0080] Gypsum provides numerous nucleation sites for the formation of ultrafine spheroidal aragonite-type calcium carbonate. The newly formed ultrafine spheroidal aragonite-type calcium carbonate adheres to the gypsum surface. Therefore, to prevent the newly formed ultrafine spheroidal aragonite-type calcium carbonate from forming a shell on the gypsum surface and hindering the reaction, this invention limits the particle size of the gypsum to ≤45 μm. This is beneficial for the complete reaction of the gypsum, avoids gypsum residue, and prevents a decrease in product purity. Further, the particle size of the aforementioned gypsum is 1-45 μm or 1-30 μm.

[0081] Considering the small grain size of ultrafine aragonite-type calcium carbonate (25-30 nm) and its good settling properties, the solid-liquid separation in step 2) is centrifugal separation. The centrifugation speed is 800-1200 r / min, and the time is 10-20 min. This effectively separates the ammonium sulfate liquid and the crude ultrafine aragonite-type calcium carbonate product. The centrifugation speed can also be 900, 1000, or 1100 r / min, and the time can be 15 min.

[0082] The following detailed description of the method for preparing ultrafine spherical aragonite-type calcium carbonate using biogas slurry is provided through specific embodiments.

[0083] Example 1

[0084] The method for preparing ultrafine spherical aragonite-type calcium carbonate using biogas slurry in this embodiment includes the following steps:

[0085] 1) Add 20g of polyaluminum chloride and 10g of cationic polyvinyl chloride amide to 200L of anaerobic fermentation biogas slurry of pig manure for flocculation treatment, and then perform solid-liquid separation treatment by pressure filtration to obtain biogas slurry;

[0086] 2) Add 2.4 kg of desulfurized gypsum to the above biogas slurry, stir at 200 r / min for 30 min to form a mixture, introduce simulated flue gas, and obtain the first material after the reaction is completed;

[0087] The reaction system was carried out in a reactor with an inner diameter of 50 cm. The simulated flue gas contained 10% carbon dioxide by volume, with the remainder being nitrogen. The flue gas flow rate was 40 L / min, the carbon dioxide flow rate was 0.64 m / min, the flow time was 120 min, and the average particle size of the desulfurized gypsum was 45 μm.

[0088] 2) Transfer the first material to a centrifuge and centrifuge at 1200 r / min for 10 min to obtain a solid phase. Wash the obtained solid phase with deionized water and centrifuge again. Repeat this process 3 times. Then place the solid phase in a drying oven for drying treatment to obtain ultrafine spherical aragonite-type calcium carbonate with a crystal size of 25-30 nm. The drying temperature is 180℃ and the drying time is 30 min.

[0089] Example 2

[0090] This embodiment is basically the same as Embodiment 1, except that: the simulated flue gas contains 100% carbon dioxide by volume percentage, the introduction time is 15 minutes, and other conditions remain unchanged.

[0091] Example 3

[0092] This embodiment is basically the same as embodiment 1, except that: in step 2), the mass of desulfurized gypsum is 4.2 kg, and other conditions remain unchanged.

[0093] Example 4

[0094] This embodiment is basically the same as embodiment 1, except that the drying temperature in step 3) is 150°C, while other conditions remain unchanged.

[0095] Comparative Example 1

[0096] This comparative example is basically the same as Example 1, except that 200L of deionized water is used instead of the anaerobic fermentation slurry of pig manure, while other conditions remain unchanged.

[0097] Comparative Example 2

[0098] This comparative example is basically the same as Example 1, except that the drying temperature in step 3) is 80°C, while other conditions remain unchanged.

[0099] Test case

[0100] 1. The following parameters of the above embodiments and comparative examples were tested:

[0101] 1) pH, suspended solids content and ammonium nitrogen content of biogas slurry: pH and suspended solids content were determined with reference to the standard "Determination of water-insoluble matter content and pH of water-soluble fertilizers" (NY / T 1973-2021), and ammonium nitrogen content was determined with reference to the standard "Determination of nitrate nitrogen, ammonium nitrogen and amide nitrogen content of fertilizers" (NY / T 1116-2014). The specific results are shown in Table 1.

[0102] 2) Average grain size: determined according to the standard "Nano Calcium Carbonate" (GB / T19590-2011), and the specific results are shown in Table 2;

[0103] 3) Purity: The purity of ultrafine spherical aragonite-type calcium carbonate was determined according to the standard "Analytical Methods for Calcium Carbonate" (GB / T 19281-2014). The specific results are shown in Table 2.

[0104] 4) Electron micrographs of the product: Electron micrographs of the product were taken using a scanning electron microscope. Figure 2 Here are electron microscope images of the product from Example 1. Figure 3 Here are electron microscope images of the product from Example 2. Figure 4 Here are electron microscope images of the product from Example 3. Figure 5 Here is an electron microscope image of the product from Example 4. Figure 6 Here are electron microscope images of the product in Comparative Example 1. Figure 7 Electron microscope images of product 2 (Comparative Example 2);

[0105] 5) XRD pattern: The crystal structure of the product was tested using an X-ray diffraction spectrometer. Figure 8 The XRD pattern of the product in Example 1 is shown below. Figure 9 The XRD pattern of the product in Example 2 is shown below. Figure 10 The XRD pattern of the product in Example 3 is shown. Figure 11 The XRD pattern of the product in Example 4 is shown. Figure 12 The image shows the XRD pattern of the product in Comparative Example 1. Figure 13 The image shows the XRD pattern of product 2 in Comparative Example 2.

[0106] 2. Test Results

[0107] Table 1 Basic Properties of Biogas Slurry

[0108]

[0109] Table 1 shows that in Examples 1-4 and Comparative Example 2, the pH, suspended solids content, and ammonium nitrogen content of the biogas slurry obtained by pretreatment of pig manure anaerobic fermentation biogas slurry all meet the requirements of this application and can be used to prepare ultrafine spherical aragonite-type calcium carbonate.

[0110] Table 2. Average grain size, purity, and crystal form of the products.

[0111]

[0112]

[0113] Table 2 and Figure 2-13 The overall results show that the products of Examples 1-4 are high-purity ultrafine aragonite-type calcium carbonate, while the products of Comparative Examples 1 and 2 are calcite-type calcium carbonate with larger grain size.

[0114] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing ultrafine spherical aragonite-type calcium carbonate using biogas slurry, characterized in that, Includes the following steps: 1) Add gypsum to the biogas slurry to form a mixture, introduce carbon dioxide gas, and obtain the first material after the reaction is complete; The biogas slurry has a pH of 8-10, a suspended solids content of ≤2000 mg / L, and an ammonium nitrogen content of ≥1000 mg / L. 2) The first material is subjected to solid-liquid separation, and the obtained solid phase is dried to obtain ultrafine spherical aragonite-type calcium carbonate with a crystal size of 25-30 nm, wherein the drying temperature is 150-600 ℃.

2. The method according to claim 1, characterized in that, Before step 1), the process also includes pretreatment of the biogas slurry stock solution to obtain the biogas slurry; The pretreatment includes at least flocculation treatment, pH adjustment treatment, and solid-liquid separation treatment.

3. The method according to claim 2, characterized in that, Flocculation treatment includes using at least one of inorganic flocculants and organic flocculants.

4. The method according to any one of claims 1-3, characterized in that, The drying process is carried out at a temperature of 169-180℃.

5. The method according to any one of claims 1-4, characterized in that, The carbon dioxide-based gases include at least one of the following: flue gas from coal combustion, flue gas from gas combustion, a mixture of carbon dioxide and nitrogen, and pure carbon dioxide.

6. The method according to claim 5, characterized in that, The volume concentration of carbon dioxide in the carbon dioxide-based gas is >10%.

7. The method according to claim 6, characterized in that, In step 1), the flux of carbon dioxide into the radial cross-section of the reaction system is 0.32-0.64 m / min; the flux of carbon dioxide into the radial cross-section of the reaction system refers to the flux of carbon dioxide along the flow direction when the radial cross-sectional area of ​​the carbon dioxide gas is equal to the radial cross-sectional area of ​​the reaction system after the carbon dioxide gas diffuses into the reaction system.

8. The method according to any one of claims 1-7, characterized in that, The mass ratio of ammonium nitrogen in the gypsum and the biogas slurry is 13:(3-6).

9. The method according to any one of claims 1-8, characterized in that, The gypsum has a particle size ≤45μm.

10. The method according to any one of claims 1-9, characterized in that, In step 2), the solid-liquid separation is centrifugal separation, wherein the centrifugal separation speed is 800-1200 r / min and the time is 10-20 min.

Citation Information

Patent Citations

  • Preparation method of high-purity vaterite type calcium carbonate microspheres

    CN111777089A

  • Method for preparing vaterite by efficiently trapping CO2 tail gas and carrying out solventing-out crystallization

    CN117658190A